PENGARUH KEAKTIFAN ORGANISASI TERHADAP PRESTASI BELAJAR MAHASISWA MANAJEMEN PENDIDIKAN ISLAM UIN ALAUDDIN MAKASSAR - St. Syamsudduha; Nursahwal; Juhrika Wulan Syah; Duriska (Educational Leadership: Jurnal Manajemen Pendidikan, 2022)
The Effect of Organizational Activity on Student Achievement in Islamic Education Management at Uin Alauddin Makassar Learning achievement is the result of learning from the process that has been carried out based on changes in behavior obtained from the experience of students in their interactions with the environment. The sampling technique used was purposive sampling, because the sample selected was based on the criteria of students from the 2019 and 2020 batches who were active in the organization. Data was collected by means of a questionnaire via google form and the research instrument used was a questionnaire in the form of differential semantics. Organizational activity on learning achievement of Islamic Education Management students of UIN Alauddin Makassar the effect of organizational activity on 54.76% then the remaining 45.24% is influenced by other factors. By being active in organizations, students can have a positive impact, especially on soft skills that support their learning achievements such as broad knowledge and insight, public speaking or communication skills, building relationships, increasing value or quality as students who are creative, innovative and intellectually different from students at generally.